CD8+CD122+PD-1+ Tregs Synergize With Costimulatory Blockade of CD40/CD154, but Not B7/CD28, to Prolong Murine Allograft Survival - Liu, Huazhen; Qiu, Feifei; Wang, Yuanzhong; Zeng, Qiaohuang; Liu, Cuihua; Chen, Yuchao; Liang, Chun-Ling; Zhang, Qunfang; Han, Ling; Dai, Zhenhua (Frontiers in Immunology, 2019)
A transplanted organ is always rejected in the absence of any immunosuppressive treatment due to vigorous alloimmunity. However, continuously global immunosuppression with a conventional immunosuppressant may result in severe side effects, including nephrotoxicity, tumors and infections. Tregs have been widely used to inhibit allograft rejection, especially in animal models. However, it’s well accepted that administration of Tregs alone is not satisfactory in immune-competent wild-type animals. Therefore, it’s imperative to promote Treg therapies under the cover of other approaches, including costimulatory blockade. In the present study, we demonstrated that administration of in vitro-expanded CD8+CD122+PD-1+ Tregs synergized with costimulatory blockade of CD40/CD154, but not B7/CD28, to prolong skin allograft survival in wild-type mice and to reduce cellular infiltration in skin allografts as well. Treg treatment and blockade of CD40/CD154, but not B7/CD28, also exhibited an additive effect on suppression of T cell proliferation in vitro and pro-inflammatory cytokine expression in skin allografts. Importantly, blocking B7/CD28, but not CD40/CD154, costimulation decreased the number of transferred CD8+CD122+PD-1+ Tregs and their expression of IL-10 in recipient mice. Furthermore, it’s B7/CD28, but not CD40/CD154, costimulatory blockade that dramatically reduced IL-10 production by CD8+CD122+PD-1+ Tregs in vitro, suggesting that B7/CD28, but not CD40/CD154, costimulation is critical for their production of IL-10. Indeed, infusion of IL-10-deficient CD8+CD122+PD-1+ Tregs failed to synergize with anti-CD154 Ab treatment to further prolong allograft survival. Our data may explain why blocking B7/CD28 costimulatory pathway does not boost IL-10-dependent Treg suppression of alloimmunity. Thus, these findings could be implicated in clinical organ transplantation.